The silencing of Maya women from Mamá Maquí to Rigoberta Menchú - Sanford, Victoria (Social justice, 2000)
Part of a special section on race, class, and state crime. In order to get a grasp of Guatemala's present transition from authoritarian rule and its efforts to construct a democratic society based on the rule of law, the writer argues that we must try to understand how the majority rural Maya experienced state structures of terror and how they internalized these structures as part of their individual and collective identities. She uses the concept of a “living memory of terror” to understand and contest the violence of the past and the fear that flourishes long after physical violence dissipates. She examines testimony, official discourse, and truth in popular memory in relation to the still contested reconstruction of Guatemalan history. She describes the silencing of Rigoberta Menchú and Mamá Maquín and analyzes testimonies of rural survivors of La Violencia and their efforts to rebuild their lives by way of the public assertion of memory and the reshaping of history.